Isolation, identification, and characterization of a marine Lactiplantibacillus plantarum strain with antimicrobial activity against Burkholderia contaminans - Du, Yuanshuai; Xin, Fan; Yang, Ziyi; Sui, Jiayi; Yang, Shen; Zeng, Runying; Chan, Zhuhua (Frontiers in Microbiology, 2025)
Burkholderia contaminans, an opportunistic pathogen commonly found in the food and cosmetics industries, has serious potential to cause severe human infections and industrial contamination. However, compared to traditional physical or chemical antimicrobial treatment, the novel biological antimicrobial strategies against B. contaminans have not been extensively explored. In this study, a strain with antimicrobial activity against B. contaminans was isolated from a marine grouper aquaculture pond and identified as Lactobacillus plantarum Dys01. The antimicrobial activity of L. plantarum Dys01 mainly originated from its metabolites, with a minimum inhibitory concentration (MIC) of 8 mg/mL. Component analysis indicated that the antibacterial substances of L. plantarum Dys01 primarily included organic acids, proteinaceous substances, and hydrogen peroxide, among which organic acids and proteinaceous substances played the major inhibitory roles. Additionally, the metabolites of L. plantarum Dys01 significantly inhibited the biofilm formation of B. contaminans in a dose-dependent manner. Alkaline phosphatase activity assays and propidium iodide staining revealed that metabolites produced by L. plantarum Dys01 could disrupt the cell wall and cell membrane integrity of B. contaminans. This was further confirmed by scanning electron microscopy, which showed typical morphological damage such as surface indentations and membrane rupture. Therefore, our study provided novel insights into the control of B. contaminans contamination in the food, cosmetic, and pharmaceutical industries, and laid an important theoretical foundation for the development of novel biopreservatives.